Pengembangan Game Animasi untuk Meningkatkan Aspek Nilai Agama Moral TK Muslimat NU 01 Gresik - Ika Ainun Munzilin (Journal of Islamic Education for Early Childhood, 2022)
Abstrack This study aims to determine the results of the development of animated multimedia games in distinguishing good behavior and bad behavior using a computer application, namely Power Point. This type of research is development (research and development). Data collection techniques using observation, interviews, documentation, and questionnaires. The results showed that the assessment of the material expert got an average score of 21 which had a percentage of 75% with the criteria of "Good" and the assessment of the media expert obtained an average score of 43 which had a percentage of 89.5% with the criteria of very "Good". The results of the assessment in the field trial of students got a percentage of 70% with appropriate criteria, the percentage of the parent's questionnaire was 78.5% in the "Good" category, the percentage of the teacher and school principal's questionnaire was 91.07 in the "Good" category. It was concluded that the overall learning media for animated games was "appropriate" to be used as a learning medium to introduce the difference between good and bad behavior in group A children. Keyword : Animated Games, Moral Religious Values, and Early Childhood